PREVALENCE OF SCHISTOSOMA HAEMATOBIUM INFECTION AMONG PRIMARY SCHOOL CHILDREN IN FASKARI AND FUNTUA LOCAL GOVERNMENT AREAS OF KATSINA STATE, NIGERIA - Bello, Sagir; Eberemu, E. C.; Orpin, J. B.; Ya’u, S. (FUDMA Journal of Sciences, 2024)
Schistosomiasis is a water-borne parasitic disease caused by Schistosoma; the digeic trematode found in the blood vessels of a man and livestock. This study was conducted to determine the prevalence of schistosoma haematobium infection among the Primary Schools pupils in Faskari and Funtua Local Government Areas of Katsina State. A total of 496 of urine samples were collected from children of 8 Primary Schools in the study areas; 4 from each local government. A questionnaire was used to collect socio-demographic and other exposure information to explore Schistosoma infection for urine, and urine sedimentation microscopic technique was used for sample analysis. Data were expressed in prevalence (%) and subjected to Chi-square analysis at p < 0.05. Out of the 496 children assessed, 160 (32.2%) were positive for urinary schistosomiasis. The prevalence is significantly (p<0.05) higher in Faskari Model Primary School with (48.3%). It was found from the result that, there was no significant relationship (P=6.608) between source of water and Schistosoma haematobium infection among the pupils in the study areas. There was also no statistical association (P= 1.570) between the source of water for bathing and the infection of urinary schistosomiasis among the students in the study areas. Therefore, schistosomiasis is prevalent in the study areas with Faskari local government having higher prevalence of the infection.